EFEKTIVITAS PROGRAM JAMINAN KESEHATAN BALI MANDARA (JKBM) DI KECAMATAN GIANYAR KABUPATEN GIANYAR - Candrika Dewi, Ida Ayu; Sri Budhi, Made Kembar; Marhaeni, A.A.I.N (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; Volume 01.No.02.Tahun 2012., 2012)
Development community do to get a better life. The success of an economic development can be assessed from three factors: the adequacy of the day-to-day needs, identity and freedom. The system of government has not been able to provide for the development of new developments in the health sector. Development efforts by the government especially the Bali Provincial Government for health development is the provision of free medical health insurance Bali Mandara (JKBM) to people who do not have health insurance in all counties in the province of Bali. This study aimed to determine the effectiveness of the program, the success of programs to improve the health JKBM, JKBM Program benefits, and relationship characteristics of respondents JKBM user perceptions about the benefits JKBM. Source of data used there are two primary data obtained from interviews to users JKBM and secondary data obtained from the District Office Gianyar Gianyar regency. Data collection methods used were interviews and questionnaires. The analysis tools are descriptive analysis, comparative analysis using statistical techniques Mc Nemar and Associative Analysis using Chi Square The results of the analysis of the characteristics of the respondents indicated that most users JKBM sex and men over the age of 46 years. In addition, most educational level is complete primary school, most of the user's work and trader user revenues ranging between $ 100000-499000 per month JKBM Program Effectiveness in Gianyar district at 93.75 percent, which means the level of effectiveness of the JKBM in Gianyar Gianyar district in the categorized as very effective. Additionally JKBM Program success can be concluded that the program JKBM can improve public health in the District of Gianyar. Greatest benefit is perceived JKBM users reduce their health expenditure. The results of the analysis of the characteristics of users with their perceptions of the benefits JKBM concluded that there are significant relationships between the characteristics of the respondents to the perceptions of the benefits JKBM Program. JKBM program that has been performing well this should always evaluate the implementation in order to better future and to improve the welfare of the community, especially people who do not have health insurance. Keywords: Effectiveness, Health Insurance, Program